A novel approach for the removal of Pb2+ and Cd2+ from wastewater by sulfur-ferromagnetic nanoparticles (SFMNs). (January 2022) - Song, Hewei; Kumar, Amit; Zhang, Yuling
Abstract: In the recent decades, due to rapid increase in industrialization, urbanization, anthropogenic activity in the catchments, removal of heavy metals contaminants in wastewater has become global challenges. Numerous advance technologies have been introduced to deal with these problems but failed in reducing adequate pollution load in the contaminated water and/or wastewater. In this study, sulfur-ferromagnetic nanoparticles (SFMNs) were synthesized by modification of nano-Fe3 O4, which can be rapidly separated from the environment by an external magnetic field after in situ repair. Its structure and physical properties were characterized by conventional techniques included Transmission electron microscope (TEM), X-ray diffraction (XRD) and vibrating sample magnetometer (VSM). The ability of the SFMNs to remove Pb 2+ and Cd 2+ was studied at different temperatures and initial metal ions concentrations. The adsorption kinetics showed that the adsorption equilibrium time of Pb 2+ and Cd 2+ was 300 min consequently adsorption process of SFMNs fit well (R 2 > 0.99) with pseudo-second-order model. The adsorption thermodynamics showed that the adsorption of Pb 2+ and Cd 2+ on SFMNs is spontaneous (negative value of ΔG 0 ) endothermic process (positive value of ΔH 0 ) and fit well (R 2 > 0.98) with the Langmuir isothermal model. Density functional theory (DFT) calculations show that SFMNs can transfer electrons to Pb 2+ and Cd 2+, and the metal ions form stable chelates on the ligand surface. This study implies that newly synthesized sulfur-ferromagnetic nanoparticles could play an instrumental role in metal ions removal from water and wastewater. Highlights: Sulfur-ferromagnetic nanoparticles (SFMNs) were obtained by modified nanomagnets. SFMNs have good adsorption effect on Pb 2+ and Cd 2+ . The adsorption process satisfies pseudo-second-order model(R 2 > 0.99). The process of adsorption is a spontaneous, endothermic reaction. Pb 2+ and Cd 2+ form stable chelates on the surface of SFMNs.